The mechanism of microglia-mediated immune inflammation in ischemic stroke and the role of natural botanical components in regulating microglia: A review - Zeng, Jinsong; Bao, Tingting; Yang, Kailin; Zhu, Xiaofei; Wang, Shanshan; Xiang, Wang; Ge, Anqi; Zeng, Liuting; Ge, Jinwen (Frontiers in Immunology, 2023)
Ischemic stroke (IS) is one of the most fatal diseases. Neuroimmunity, inflammation, and oxidative stress play important roles in various complex mechanisms of IS. In particular, the early proinflammatory response resulting from the overactivation of resident microglia and the infiltration of circulating monocytes and macrophages in the brain after cerebral ischemia leads to secondary brain injury. Microglia are innate immune cells in the brain that constantly monitor the brain microenvironment under normal conditions. Once ischemia occurs, microglia are activated to produce dual effects of neurotoxicity and neuroprotection, and the balance of the two effects determines the fate of damaged neurons. The activation of microglia is defined as the classical activation (M1 type) or alternative activation (M2 type). M1 type microglia secrete pro-inflammatory cytokines and neurotoxic mediators to exacerbate neuronal damage, while M2 type microglia promote a repairing anti-inflammatory response. Fine regulation of M1/M2 microglial activation to minimize damage and maximize protection has important therapeutic value. This review focuses on the interaction between M1 / M2 microglia and other immune cells involved in the regulation of IS phenotypic characteristics, and the mechanism of natural plant components regulating microglia after IS, providing novel candidate drugs for regulating microglial balance and IS drug development.